Mean induction time and isothermal kinetic analysis of methane hydrate formation in water and imidazolium based ionic liquid solutions. (February 2018) - Nashed, Omar; Sabil, Khalik M.; Ismail, Lukman; Japper-Jaafar, Azuraien; Lal, Bhajan
Highlights: Mean induction time of methane hydrate in presence IL solutions is measured. [BMIM][CF3 SO3 ], [BMIM][CH3 SO4 ], and [OH-EMIM][Br] acted as kinetic methane inhibitors. Avrami model has a good fit with experimental data during hydrate crystallization process. Methane hydrate crystals can be formed in one or two dimension. Abstract: In this work, the performance of nine ionic liquids (ILs) as kinetic inhibitors for methane gas hydrates is investigated employing a high pressure micro differential scanning calorimeter (HPµDSC). Aqueous IL solutions of 0.01 mass fraction, as well as poly vinyl pyrrolidone (PVP), are prepared and the induction time of methane hydrate formation in these solutions is measured at 7.1 MPa and 258.15 K. It is found that [BMIM][CF3 SO3 ], [BMIM][CH3 SO4 ], and [OH-EMIM][Br] can delay hydrate formation at this concentration. Their relative inhibition power (RIP) are higher than PVP. The other ILs exhibit shorter induction time when compare with the blank sample, which shows their promotional effect rather than inhibition effect. It is found that there is a strong correlation between molar mass of [BMIM] + based ILs and induction time. An attempt to model the kinetic of methane hydrate formation in the presence of low dosage ILs has been carried out using Avrami model by utilizing isothermal hydrate crystallization data. The kinetic analysis shows the needle like the shape of the nuclei and the one dimensional crystal growth during the methane hydrate formation. The Avrami analysis also indicates that most of the crystallization process of methane hydrate is governed by the enclathration reaction and slightly leads by the diffusion-controlled mechanism.